Students and teachers’ perception about the writing process - Campaña Pallasco, Gissela Jacqueline (2016)
The main aim of this research was to identify the tenth grade students and teachers’ perceptions respect to the teaching of English writing skill. A survey of 14 question were applied to fifty eight tenth graders of Jorge Icaza Educative Unit, Latacunga- Ecuador in order to identify their perception regarding to writing skill and the methodology teachers use to teach it. In addition, a survey of 17 questions were applied to English teachers of institutions that belong to Eloy Alfaro Parish, Latacunga Ecuador in order to know their beliefs about how and when to teach writing skill. Data were processed in excel and presented in graphics. The analysis was done by pointed out the main findings; concepts form literature reviews and researchers’ point of view. Results of students’ survey show that they are not able to write simple pieces of writing like paragraphs, letters, stories and personal experiences because there is not an appropriate process of writing practice in the classroom. Writing is given little attention by teachers and students and its practice is not regular into the classroom….